Pendugaan Area Kecil untuk Persentase Anak Usia 7—17 Tahun yang Tidak Sekolah Level Kabupaten/Kota di Pulau Sumatera Tahun 2023 - Wisly Ryanr Elieze; Karina Himalaya; Afidita Nabila Putri; Aditya Prameswara Achmadi; Azka Ubaidillah; Shafiyah Asy Syahidah; Aisyah 'Azizah Nur Rahmah (Jurnal Matematika, Statistika dan Komputasi, 2024)
Ensuring the quality of education is a fundamental commitment towards achieving sustainable development goals (SDGs). One effective strategy to enhance education quality is addressing the high number of children out of school. More precise district/city-level data on the percentage of out-of-school children needs to be provided. Estimation results from Susenas data show that Sumatra Island has the highest proportion of districts/cities with a Relative Standard Error (RSE) of over 25% compared to other islands in Indonesia. Therefore, this study applies Hierarchical Bayes (HB) Beta method by utilizing accompanying variables. The research reveals that the HB Beta estimator is the most effective in estimating the percentage of out-of-school children aged 7—17 years at the district/city level on Sumatra Island. The Small Area Estimation (SAE) model offers a more precise estimate than the direct estimator. Furthermore, there are 25 districts/cities with a high percentage of children aged 7—17 years who are not in school, with the majority located in the southern region of Sumatra Island